ANALISA ASUHAN KEPERAWATAN DENGAN INTERVENSI KOMBINASI KOMPRES HANGAT DAN TEKNIK DISTRAKSI DZIKIR TERHADAP MASALAH NYERI AKUT PADA PASIEN KOLIK ABDOMEN DI RUANG TERATAI 2 RUMAH SAKIT BHAYANGKARA TINGKAT 1 RADEN SAID SUKANTO - Erina Nurbaiti, (2022)
Abdominal colic is a condition characterized by the appearance of pain originating from the organs in the abdomen, namely an obstruction in the intestine. The pain felt is visceral pain that can continue to develop progressively and cause a visceral phenomenon, namely vomiting. In pain management, one of the independent actions that a nurse can take is to provide non-pharmacological management to patients with abdominal colic by providing complementary therapy. Complementary therapy applied in this study is the combination of warm compresses and dhikr distraction techniques. The purpose of this study was to determine whether the provision of complementary therapeutic innovation interventions could have an effect in overcoming the problem of acute pain in abdominal colic patients in Teratai 2 Room Bhayangkara Hospital Level 1 Raden Said Sukanto. Pain measurement used is Numeric Rating Scale (NRS). After nursing actions for 3 x 24 hours with the provision of warm compress therapy and dhikr distraction techniques, it was found that the acute pain problem in managed patients had not been resolved, there was only a decrease in the pain scale after the intervention but there was no significant decrease in pain intensity, while acute pain problems in patients Resume resolved. The difference in pain scale changes in the two patients was influenced by various factors, namely differences of etiology (hernia and obstipation), different types of intestinal obstruction, age differences, and psychosocial factors, namely perception, patient tolerance, and patient experience of pain. Keywords: abdominal colic, warm compresses, acute pain, dhikr distraction technique, complementary therapy